The Level of Climate Change Science Literacy among Teachers in Seychelles: Implications for the Blue Economy - Anyanwu, Raymond Ndubisi (Asian Journal of Interdisciplinary Research, 2019)
Climate change poses a serious threat to the ocean on which the Seychelles economy depends for resources and services. To address this concern, the Seychelles National Climate Change Response Strategy recommends education about climate change in all levels of the education system to nurture young people with the capacity to address climate change impacts. This quantitative, descriptive, cross-sectional survey measures the level of climate change science literacy among teachers in Seychelles on a five-point summated scale (Extremely Low, Low, Medium, High, and Extremely High). Data was collected with a 15-item Climate Change Science Literacy Questionnaire (CCSLQ) from 572 participants representing 42.62% of the population of teachers in public schools at the time of the survey. Ethical considerations relating to access, informed consent, anonymity, and confidentiality were fulfilled. Collected data was analysed statistically with descriptive techniques (percentage, means, standard error of measurement and confidence interval) and inferential technique with the Fisher’s Exact Chi-Square test. Statistical operation was performed with the Statistical Package for the Social Science (SPSS). Results indicate that the majority of the participants (37.4%, n=214) have medium literacy regarding climate change science with misconceptions on all three domains of climate change science: causes, impacts, and solutions. Educational interventions to enhance teachers’ knowledge and understanding of climate change are recommended; otherwise the teachers will transfer inaccurate concepts to the learners. Without young Seychellois with the capacity to take action on climate change, it may be wearisome for Seychelles to achieve a smooth transition to a blue economy.
openalex:W2946512275 mag:2946512275 KerkoCite.ItemAlsoKnownAs: 10.34256/ajir1921 5072953:HJUFFRCN 5072953:I9RKQ63Z
Keywords: C:Seychelles; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change science literacy; oa:sdg:4 Quality education; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The Level of Climate Change Science Literacy among Teachers in Seychelles: Implications for the Blue Economy - Anyanwu, Raymond Ndubisi (Asian Journal of Interdisciplinary Research, 2019)
Climate change poses a serious threat to the ocean on which the Seychelles economy depends for resources and services. To address this concern, the Seychelles National Climate Change Response Strategy recommends education about climate change in all levels of the education system to nurture young people with the capacity to address climate change impacts. This quantitative, descriptive, cross-sectional survey measures the level of climate change science literacy among teachers in Seychelles on a five-point summated scale (Extremely Low, Low, Medium, High, and Extremely High). Data was collected with a 15-item Climate Change Science Literacy Questionnaire (CCSLQ) from 572 participants representing 42.62% of the population of teachers in public schools at the time of the survey. Ethical considerations relating to access, informed consent, anonymity, and confidentiality were fulfilled. Collected data was analysed statistically with descriptive techniques (percentage, means, standard error of measurement and confidence interval) and inferential technique with the Fisher’s Exact Chi-Square test. Statistical operation was performed with the Statistical Package for the Social Science (SPSS). Results indicate that the majority of the participants (37.4%, n=214) have medium literacy regarding climate change science with misconceptions on all three domains of climate change science: causes, impacts, and solutions. Educational interventions to enhance teachers’ knowledge and understanding of climate change are recommended; otherwise the teachers will transfer inaccurate concepts to the learners. Without young Seychellois with the capacity to take action on climate change, it may be wearisome for Seychelles to achieve a smooth transition to a blue economy.
openalex:W2946512275 mag:2946512275 KerkoCite.ItemAlsoKnownAs: 10.34256/ajir1921 5072953:HJUFFRCN 5072953:I9RKQ63Z
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change science literacy; oa:sdg:4 Quality education; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The influence of teacher variables on climate change science literacy of Geography teachers in the Western Cape, South Africa - Anyanwu, Raymond Ndubisi; Grange, Lesley Le (International Research in Geographical and Environmental Education, 2017)
Teachers play an important role in promoting climate change literacy in schools, but not much is known about which teacher characteristics significantly influence Geography teachers’ climate change science literacy. The purpose of this study is to determine the influence of teachers’ characteristics such as gender, age, qualification, specialisation, experience, and teaching grade on Geography teachers’ literacy about climate change science. The study uses a quantitative research approach on questionnaire application. Statistical analysis of data gathered from 194 high school Geography teachers from the Western Cape Province using a 15-item Climate Change Science Literacy Questionnaire (CCSLQ) revealed that gender, age, teaching experience, and teaching grade significantly influenced Geography teachers’ literacy about climate change science, while qualification and specialisation did not.
openalex:W2615487877 mag:2615487877 KerkoCite.ItemAlsoKnownAs: 10.1080/10382046.2017.1330039 5072953:4XSZN7U3
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change science literacy; oa:keyword:geography teachers; oa:sdg:13 Climate action; oa:topic:T10072 Enhancing Science Education through Inquiry and Argumentation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change science: The literacy of Geography teachers in the Western Cape Province, South Africa - Anyanwu, Raymond Ndubisi; Grange, Lesley Le; Beets, Peter (South African Journal of Education, 2015)
One of the universal responses to tackling global climate change is teaching climate change concepts at all levels of formal education. This response requires, among other things, teachers who are fully literate about climate change science, so that they can explain the concepts underlying the causes, impacts and solutions of climate change as accurately as possible to learners. The main intention of this study was to understand high school Geography teachers’ levels of knowledge about climate change science. A 15-item, criterion-referenced, multiple-choice Climate Change Literacy Questionnaire with a reliability coefficient of 0.74 using the Guttman’s spit-half test was administered to 194 high school Geography teachers in the Western Cape Province of South Africa. Data collected were analysed with the Pearson’s Chi-square test and One-Way Analysis of Variance (ANOVA). The results showed that the majority of the participants demonstrated significantly high literacy levels in climate science, with their literacy levels higher in climate processes and causes of climate change than climate change impacts and solutions. Misconceptions were found in all three categories of climate change science as represented in the survey instrument. These findings suggest that teacher educators and policymakers should improve professional development programmes and support interventions in teacher knowledge and understanding of climate change concepts, so as to enhance climate change education in schools.Keywords: climate change education; climate change misconceptions; climate change science literacy; Geography teachers; survey research
openalex:W1834233692 mag:1834233692 KerkoCite.ItemAlsoKnownAs: 10.15700/saje.v35n3a1160 5072953:MTERCZVW
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change science; oa:keyword:geography teachers; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12904 Agricultural Education and School Gardening Research; oa:topic:T13435 Human Attitudes and Interactions with Animals and Plants; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found